2006
DOI: 10.1152/ajpendo.00608.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of portal glucose delivery on glucose metabolism in conscious, unrestrained mice

Abstract: Previous studies in mice suggest that portal venous infusion of glucose at a low rate paradoxically causes hypoglycemia; this does not occur in dogs, rats, and humans. A possible explanation is that fasting status in the mouse studies may have altered the response. We sought to determine whether the response to portal glucose delivery in the mouse was similar to that seen in other species and whether it was dependent on fasting status. Studies were performed on chronically catheterized conscious mice. Catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The main focus of this study was the liver, since it is a primary regulator of the nutrient supply to the other tissues and organs, because ingested carbohydrates and AAs go to the liver via the portal vein before entering the systemic circulation. In the presence of the portal glucose signal, net hepatic glucose uptake in the current studies was greater than during peripheral glucose delivery, as demonstrated in previous studies (15,25,39,47). In the current case (portal vein AA infusion), the hepatic fractional extraction of glucose was augmented fourfold by the portal glucose signal.…”
Section: Hepatic Metabolismsupporting
confidence: 79%
See 1 more Smart Citation
“…The main focus of this study was the liver, since it is a primary regulator of the nutrient supply to the other tissues and organs, because ingested carbohydrates and AAs go to the liver via the portal vein before entering the systemic circulation. In the presence of the portal glucose signal, net hepatic glucose uptake in the current studies was greater than during peripheral glucose delivery, as demonstrated in previous studies (15,25,39,47). In the current case (portal vein AA infusion), the hepatic fractional extraction of glucose was augmented fourfold by the portal glucose signal.…”
Section: Hepatic Metabolismsupporting
confidence: 79%
“…In a previous study in which only gluconeogenic AAs (as opposed to all AAs) were infused intraportally along with glucose, the portal glucose signal seemed to be blunted (38). The portal glucose signal has been associated with a translocation of glucokinase from the nucleus to the cytoplasm in the liver of rats and mice, where it exerts its activity and induces increased glucose uptake and glycogen synthesis (14,15). Under postprandial conditions, one of the major fates of gluconeogenic AAs in the liver is glycogen synthesis (6).…”
Section: Hepatic Metabolismmentioning
confidence: 97%
“…Such a purity criterion leaves room for nonnegligible amounts of radioactive impurities, which could have been carried to the glucose isolated from the venous blood. Also, the amount of radioactivity counted in glucose was a minuscule fraction of the radioactivity infused as [U- 14 In 1986, Hahn & Wei-Ning (28) reported data from incubations of fragments of small intestinal mucosa of rats or rabbits in KrebsRinger bicarbonate buffer containing 10 mM unlabeled glutamate and 10 mM [ 14 C]lactate. They reported low rates of gluconeogenesis from lactate in the intestinal mucosa of suckling rats and rabbits.…”
Section: Measurements Of Rates Of Intestinal Gluconeogenesismentioning
confidence: 99%
“…The blood flow through the small intestine was measured using radioactive microspheres in other rats, similarly prepared but not infused with [3-3 H]glucose (39). [3-3 H]Glucose is commonly used to trace glucose metabolism (14,33) because all its label is released to [ 3 H]water when the hexose skeleton is split to triose phosphates. Thus, a simple way to measure the specific activity of plasma glucose involves (a) deproteinization of plasma, (b) assay of glucose concentration in the protein-free extract, and (c) complete evaporation of the extract to eliminate [ 3 H]water, followed by redissolution in water, and liquid scintillation counting.…”
Section: Measurements Of Rates Of Intestinal Gluconeogenesismentioning
confidence: 99%
“…A positive differential in glucose concentration between the portal vein and hepatic artery, as results from feeding, increases hepatic glycogen synthesis. This so-called "portal signal" [5] has been observed in several species [6,7] and has been shown to be likely neurally mediated [8]. Lastly, hepatic glycogen synthesis is under tight hormonal control.…”
Section: Introductionmentioning
confidence: 85%